Postural Control and Interceptive Skills in Children With Autism Spectrum Disorder. Issue 9 (11th June 2019) - Chen, Li-Chiou; Su, Wan-Chun; Ho, Tzu-Lin; Lu, Lu; Tsai, Wen-Che; Chiu, Yen-Nan; Jeng, Suh-Fang
Abstract: Background: Increasing evidence shows common motor deficits associated with autism spectrum disorder (ASD) that can relate to impaired planning and control processes of the sensorimotor system. Catching is a fundamental motor skill that requires coordination between vision, posture, and arm movements. Although postural control and ball catching have been shown to be impaired in children with ASD, previous studies have not investigated how these components are integrated. Objective: The objective of this study was to investigate the sensorimotor control of arm movements and postural adjustments during ball catching in children with and without ASD. Design: This study employed a cross-sectional design. Methods: Fifteen children with ASD (mean [SD] age = 8.8 [1.2] years; 12 boys) and 15 age- and sex-matched typically developing children participated in this study. Children were asked to catch a ball rolling down a ramp in 6 test conditions in which visual inputs and ramp direction were manipulated to provide different sensory conditions and postural demands. Results: Compared with their typically developing peers, children with ASD had increased difficulties catching balls, especially those from lateral directions. They less often used visual information to plan for catching motion, demonstrated fewer and delayed anticipatory postural adjustments, and exhibited increased corrective control. Limitations: The sample excluded children with intellectual disability and attention deficit and hyperactivity disorders that might reduce the generalizability to the whole ASD population. Conclusions: Our results suggest that motor difficulties present in children with ASD can result from compromised sensorimotor integration in planning and control of movements.